Influence of hydrogen on the propagation of intergranular corrosion defects in 2024 aluminium alloy. (March 2019) - de Bonfils-Lahovary, Marie-Laetitia; Josse, Claudie; Laffont, Lydia; Blanc, Christine
Graphical abstract: Highlights: H did not influence the elementary processes of intergranular corrosion. H had a significant impact on the local reactivity of 2024 aluminium alloy. In the presence of H, the number of corroded interfaces strongly increased. H led to embrittlement of subgrain boundaries and CSL grain boundaries. H-induced changes led to a ramification of intergranular corrosion defects. Abstract: To study the influence of hydrogen on the intergranular corrosion mechanism of a 2024 aluminium alloy, samples were hydrogen precharged by cathodic polarisation and then exposed to a NaCl solution. EBSD analyses and SEM observations showed that hydrogen increased the number of corroded interfaces and led to the embrittlement of low-angle grain boundaries which were not susceptible to corrosion without hydrogen precharging. The increase of the reactivity of the 2024 aluminium alloy in the presence of hydrogen gave a new insight into the intergranular corrosion mechanism: corrosion-induced hydrogen promoted the intergranular corrosion propagation and partially controlled the corrosion defect morphology.